ARCHITECTURAL COMPETITIONS AS A SEARCH FOR NEW SOLUTIONS AND THEIR IMPACT ON THE FORMATION OF MODERN ARCHITECTURAL IDEAS (Municipal economy of cities (Technical science), 2013)
The features of architectural competitions, analyzed their methods and forms of organization, as well as factors that have influence on the formation of new architectural ideas.